Dielectric Properties and Interfacial Phenomena of Metal/Insulator/Metal (MIM) Devices of Phosphatidic acid LangmuirÂ¬Blodgett Films - Abdul Majid, Wan Haliza; Rasat Muhamad, Muhamad (Malaysian Journal of Science, 2008)
The interfacial phenomena of metal/insulator (organic)/metal (MIM) devices of the phospholipid Langmuir-Blodgett (LB) films have been investigated. Two types of phospholipids with different length of alkyl chains i.e. 1,2-dimyristoyl-sn-glycero-3-phosphatidic acid (DMPA) and 1,2- dipalmitoyl-sn-glycero-3-phosphatidic acid (DPPA), were used in this study. The variations of capacitance and conductance of the MIM devices were examined as a function of number of LB layers as well as frequency. The results obtained from the measurements indicate that the phospholipid LB films sandwiched between two aluminium electrodes behave as a good insulator. The dielectric constants of 3.0 and 3.3 have been calculated for DMPA and DPPA monolayers respectively. The capacitance results also revealed that the devices consist of a native oxide layer of Al203 between the bottom aluminium electrode and the LB films. In this particular case, it has been evaluated that the oxide layer is about 25 A. In general, the plots of conductance as a function of frequency of the MIM devices exhibit logarithmic variation.